New Species and First Record of Dannella Edmunds 1959 (Ephemeroptera: Ephemerellidae) from the Eastern Palaearctic - Tiunova, Tatiana M. (Zootaxa, 2023)
A new species, Dannella daurica sp. nov. is described from the Far East of Russia, based on larvae. Characters of this new species agree with the diagnosis of Dannella Edmunds 1959 in the restricted sense. Comparison of the larva of Dannella daurica sp. nov. with other known larvae of Dannella is given. Until now, the genus Dannella was known only from the Nearctic Region. This is the first report of this genus from the East Palaearctic Region.